Electrocatalysts: Multigrain Platinum Nanowires Consisting of Oriented Nanoparticles Anchored on Sulfur‐Doped Graphene as a Highly Active and Durable Oxygen Reduction Electrocatalyst (Adv. Mater. 7/2015). (February 2015) - Hoque, Md Ariful; Hassan, Fathy M.; Higgins, Drew; Choi, Ja‐Yeon; Pritzker, Mark; Knights, Shanna; Ye, Siyu; Chen, Zhongwei
<x xml:space="preserve">Abstract</x> Z. Chen and co‐workers report direct growth of multigrain platinum nanowires (NWs) on sulfur‐doped graphene (SG) on page 1229. It is found that the nanowires are composed of numerous single‐crystalline nanoparticles that are attached and oriented along the <111> crystallographic direction. Notably, PtNW/SG exhibits excellent electrochemical oxygen reduction reaction (ORR) activity and stability in comparison with PtNW/G and commercial Pt/C catalysts under harsh potentiodynamic conditions, reduction, and dramatically improved stability through accelerated durability testing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>